Short-term Outcome of Pulmonary Hemorrhage in Very-Low-Birth-Weight Preterm Infants - Ting-An Yen; Ching-Chia Wang; Wu-Shiun Hsieh; Hung-Chieh Chou; Chien-Yi Chen; Po-Nien Tsao (Pediatrics and Neonatology)
Severe pulmonary hemorrhage is a serious complication with a high mortality rate in preterm infants with respiratory distress syndrome (RDS) after surfactant therapy. The aim of this study is to evaluate the efficacy of our current management strategy for neonates with severe pulmonary hemorrhage. Materials and methods: Very-low-birth-weight (VLBW) infants who developed severe pulmonary hemorrhage were studied from January 2006 to August 2011. Treatment for severe pulmonary hemorrhage in our neonatal intensive care unit (NICU) included intratracheal epinephrine spraying/irrigation, blood component therapy, and as necessary, surfactant supplement therapy was administered in cases that secondary RDS was diagnosed. High frequency oscillatory ventilation (HFOV) was utilized when hypoxia or respiratory acidosis persisted under conventional mechanical ventilation (CMV). We then described the clinical courses of severe pulmonary hemorrhage following our management. Results: A total of 18 (3.2%) out of 469 VLBW infants developed severe pulmonary hemorrhage. The mean gestational age was 27 weeks, the mean birth weight was 822 g, and the onset age was 2.5 days after birth. There was no severe pulmonary hemorrhage-associated mortality during this period with the exception of one case, in which an infant died after the parents refused to do further therapy. Sixteen (88.8%) neonates had RDS and 13 received surfactant therapy. Twelve (66.6%) cases developed secondary RDS following the onset of severe pulmonary hemorrhage, and four cases received surfactant supplement therapy. In the surfactant supplement group, alveolar-arterial oxygen difference (AaDO2) and oxygenation index (OI) during the 2–4 hours postpulmonary hemorrhage period showed statistically significant improvement, whereas the other group only showed a tendency toward improvement without reaching statistical significance when compared to the baseline data. Duration of high oxygen requirement [defined as fraction of inspired oxygen (FiO2) > 40%] was also less in the surfactant supplement group. Conclusion: This data suggests that our current strategy is effective for treating severe pulmonary hemorrhage in VLBW infants. Surfactant therapy for severe pulmonary hemorrhage may also be beneficial for improving lung function and may shorten the duration of high oxygen requirement.